2018
DOI: 10.2465/jmps.171201
|View full text |Cite
|
Sign up to set email alerts
|

Laser step–heating <sup>40</sup>Ar/<sup>39</sup>Ar analyses of biotites from meta–granites in the UHP Brossasco–Isasca Unit of Dora–Maira Massif, Italy

Abstract: Two undeformed metagranite samples were collected from the UHP Brossasco-Isasca Unit (BIU) of Dora-Maira Massif, Italy to carry out the laser step-heating 40 Ar/ 39 Ar analyses of individual biotite crystals. The metagranites occur as undeformed domains (m-to ten of meters in size) within strongly deformed augen-gneiss. They still preserve their medium-to coarse-grained igneous texture and are composed mainly of K-feldspar, plagioclase pseudomorph, quartz, and biotite that preserve their original igneous shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Itaya et al [57] reported excess argon-bearing K-feldspar from metagranite in the UHP Brossasco-Isasca Unit of Dora Maira Massif, Italy, and pointed out the possibility that K-feldspar has trapped the EAW generated by the argon release from micas during the exhumation and cooling of the host lithologies. Itaya et al [58] carried out laser step-heating 40 Ar/ 39 Ar analyses of biotite from the same metagranite and found the biotite crystals which have old age fractions (800 to Another example is represented by some kyanite grains from the river sand in NE Japan, which gave extremely old 40 Ar/ 39 Ar ages (8-6 Ga: [54]). These very old ages have been interpreted as due to the fact that kyanite recrystallized in the host rocks under ultra-high argon pressure derived from radiogenic argon in potassium-rich phases such as phengites during the Barrovian-type retrogression of UHP rocks.…”
Section: Figure A2mentioning
confidence: 99%
See 1 more Smart Citation
“…Itaya et al [57] reported excess argon-bearing K-feldspar from metagranite in the UHP Brossasco-Isasca Unit of Dora Maira Massif, Italy, and pointed out the possibility that K-feldspar has trapped the EAW generated by the argon release from micas during the exhumation and cooling of the host lithologies. Itaya et al [58] carried out laser step-heating 40 Ar/ 39 Ar analyses of biotite from the same metagranite and found the biotite crystals which have old age fractions (800 to Another example is represented by some kyanite grains from the river sand in NE Japan, which gave extremely old 40 Ar/ 39 Ar ages (8-6 Ga: [54]). These very old ages have been interpreted as due to the fact that kyanite recrystallized in the host rocks under ultra-high argon pressure derived from radiogenic argon in potassium-rich phases such as phengites during the Barrovian-type retrogression of UHP rocks.…”
Section: Figure A2mentioning
confidence: 99%
“…Itaya et al [57] reported excess argon-bearing K-feldspar from metagranite in the UHP Brossasco-Isasca Unit of Dora Maira Massif, Italy, and pointed out the possibility that K-feldspar has trapped the EAW generated by the argon release from micas during the exhumation and cooling of the host lithologies. Itaya et al [58] carried out laser step-heating 40 Ar/ 39 Ar analyses of biotite from…”
Section: Figure A2mentioning
confidence: 99%
“…This crystal appears to be significantly older than 2000 Ma in the middle temperature fractions, suggesting that excess argon is trapped in the biotite crystal. Biotite may happen to trap the excess argon waves that occurred in the contact aureoles [27] and in the regional metamorphic belts such as the Barrovian-type metamorphic belt, the eastern Tibetan Plateau [28] and the Dora Maira Massif of Western Alps, Italy [29]. This suggests that the Acasta gneiss originally contained biotite.…”
Section: Laser Step-heatingmentioning
confidence: 99%
“…In situ 40 Ar/ 39 Ar ultraviolet (UV) laser-ablation spot analyses is one of the most used methods for giving absolute time constraints and, in particular, data obtained from minerals oriented along metamorphic foliations provide ages of deformation (see e.g. Itaya et al, 2018;Wiederkehr et al, 2009;Villa et al, 2014 and reference therein).…”
Section: Introductionmentioning
confidence: 99%